Homonyms in Sayat-Nova’s poems - Torabi, Maryam (Bulletin of Yerevan University B: Philology, 2022)
In the rich vocabulary of the poems of the 18the century Armenian poet(ashugh) Sayat-Nova, many homonyms are used. Various borrowings, dialectical units, special usage of words in the words of the ashugh for by  the requirements of the poetic and artistic style, created a series of homonyms.In this article, the author presents the homonyms that exist in the poems of Sayat-Nova. The presented homonymous formations have semantic, speech, grammatical and root varieties.In this regard, two-membered, three-membered, four-membered and five-membered homonymous formations are singled out.
Keywords: Sayat-Nova; poem; homonyms; dialect; middle armenian language(Grabar); loan words